The relationship between mathematical literacy and the realistic mathematic education approach: A systematic literature review - A'la, Nurul; Cut Morina, Zubainur; Elizar, Elizar (Universitas Islam Negeri (UIN) Mataram, 2025)
[English]: This systematic literature review (SLR) explores the relationship between mathematical literacy and the Realistic Mathematics Education (RME) approach, which emphasizes the use of real-world contexts in mathematics instruction. This review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to ensure transparency and rigor in the selection, analysis, and synthesis of relevant studies. The review examines studies published between 2019 and 2024, focusing on trends, research methodologies, and the effectiveness of RME in enhancing students' mathematical literacy. The evidence suggests a potential relationship between the implementation of RME and students tendencies to demonstrate a better grasp of mathematical concepts, as well as a stronger inclination toward solving problems in context-based settings. These findings, while drawn from limited and non-randomized studies, suggest that RME may be associated with more meaningful student engagement in mathematics.The review also identifies the research instruments frequently used in RME-related studies and highlights the importance of contextualized learning in promoting mathematical literacy. Despite challenges, such as the need for more innovative, contextually relevant learning designs and the adaptation of RME across various educational settings, the approach has proven to be an effective strategy for advancing students' mathematical literacy, critical thinking, and problem-solving abilities. These findings contribute to the growing body of research that advocates for context-driven approaches in mathematics education. [Bahasa]: Tinjauan literatur sistematis (SLR) ini mengeksplorasi hubungan antara literasi matematika dan pendekatan Pendidikan Matematika Realistik (RME), yang menekankan penggunaan konteks dunia nyata dalam pengajaran matematika. Kajian ini mengkaji studi yang diterbitkan antara tahun 2019 dan 2024, dengan fokus pada tren, metodologi penelitian, dan efektivitas RME dalam meningkatkan literasi matematika siswa. Temuan menunjukkan bahwa RME secara signifikan meningkatkan pemahaman siswa tentang konsep matematika dan memperkuat keterampilan pemecahan masalah mereka dengan menggabungkan pengalaman belajar berbasis konteks yang praktis. Tinjauan ini juga mengidentifikasi instrumen penelitian yang sering digunakan dalam penelitian terkait RME dan menyoroti pentingnya pembelajaran kontekstual dalam mempromosikan literasi matematika. Terlepas dari tantangan yang ada, seperti kebutuhan akan desain pembelajaran yang lebih inovatif dan relevan secara kontekstual serta adaptasi RME di berbagai lingkungan pendidikan, pendekatan ini telah terbukti menjadi strategi yang efektif untuk memajukan literasi matematika siswa, berpikir kritis, dan kemampuan pemecahan masalah. Temuan-temuan ini berkontribusi pada penelitian yang terus berkembang yang mendukung pendekatan berbasis konteks dalam pendidikan matematika.